Intermetallic compounds and choice of alloying elements for the manufacture of thixomolded creepresistant magnesium alloys - Goryany V.; Mauk P.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This study aims at finding ways to improve the service properties of state-of-the-art creepresistant Mg alloys for Thixomolding and minimise production problems. In doing so, microalloying with Si, Zn, Sr, Li, C, Ba and Bi, as well as the addition of rare earths is a viable solution. .